2023
DOI: 10.1021/acsnano.2c11567
|View full text |Cite
|
Sign up to set email alerts
|

Se-Vacancy Healing with Substitutional Oxygen in WSe2 for High-Mobility p-Type Field-Effect Transistors

Abstract: Transition-metal dichalcogenides possess high carrier mobility and can be scaled to sub-nanometer dimensions, making them viable alternative to Si electronics. WSe2 is capable of hole and electron carrier transport, making it a key component in CMOS logic circuits. However, since the p-type electrical performance of the WSe2-field effect transistor (FET) is still limited, various approaches are being investigated to circumvent this issue. Here, we formed a heterostructural multilayer WSe2 channel and solution-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Metal chlorides, such as SnCl 4 , FeCl 3 , and AuCl 3 , have also been explored as chemical dopants for p -type TMD flakes . Another strategy is to use oxygen doping from inorganic aluminum-doped zinc oxide to the WSe 2 channel that can heal Se deficiency and achieve high-mobility p -type FETs . But the chemical doping approaches are facing challenges in material and performance robustness at an elevated temperature (e.g., >100–200 °C) or continual electrical bias due to the relatively unstable molecular doping.…”
Section: Discussionmentioning
confidence: 99%
“…Metal chlorides, such as SnCl 4 , FeCl 3 , and AuCl 3 , have also been explored as chemical dopants for p -type TMD flakes . Another strategy is to use oxygen doping from inorganic aluminum-doped zinc oxide to the WSe 2 channel that can heal Se deficiency and achieve high-mobility p -type FETs . But the chemical doping approaches are facing challenges in material and performance robustness at an elevated temperature (e.g., >100–200 °C) or continual electrical bias due to the relatively unstable molecular doping.…”
Section: Discussionmentioning
confidence: 99%
“…(f) Comparison of μ h and on–off ratio for pristine and O-doped WSe 2 transistors. Reproduced with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Treatments For Chalcogen Vacanciesmentioning
confidence: 99%
“…The electronic properties of WSe 2 -based FETs can be improved by reducing the SeVs through aluminum zinc oxide (AZO) treatment . The AZO treatment process, which is performed in solution, includes the following steps: spin-coating on WSe 2 FETs, annealing, and wet etching (Figure e).…”
Section: Treatments For Chalcogen Vacanciesmentioning
confidence: 99%
“…Recently, two-dimensional (2D) transition metal dichalcogenides (TMDs), such as MoS 2 , MoSe 2 , WS 2 , and WSe 2 , have attracted tremendous attention as next-generation semiconductors due to their fascinating electrical and optical properties. The electrical properties of 2D TMD-based field effect transistors can be effectively and nondestructively tuned by coating various organic molecules on their surface due to surface charge-transfer doping or formation of heterostructures. However, many previous reports found that this may result in an increase of both ON and OFF current, severely limiting the signal-to-noise ratio (SNR) when applied to photosensing applications (i.e., phototransistors). An example of such an increase in OFF current after coating organic molecules on a 2D TMD-based transistor is shown in Figure S1. Therefore, the effective application of organic coatings on TMD-based phototransistors dictates that it is necessary to limit potential OFF current increases and act as a light absorption layer to improve the photosensitivity (i.e., SNR) of TMD-based phototransistors.…”
Section: Introductionmentioning
confidence: 99%